Antagonistic activity of selected bacteria against colletotrichum gloeosporioides in harumanis mango / Falex J.Langkan - J.Langkan, Falex (2015)
Harumanis mango is one of the most popular fruits in Malaysia and has excellent potential as an export crop. The major pre and postharvest disease of mango is anthracnose, caused by the fimgus C. gloeosporioides. Synthetic fungicides are commonly used to reduce losses from anthracnose disease. However, their use gradually become more restricted due to public concern over toxic residues. The aims of this study were to isolate the causal agent of antracnose and the antagonistic bacteria from the Harumanis mango, determine the antagonist activity of antagonist bacteria towards C. gloeosporioides in vitro, identifying the pathogen and the antagonist bacteria by 16S rDNA and screening the antifungal compounds produced by the antagonist bacteria. Twelve bacterial isolates were initially selected from 96 isolates tested which showed inhibitory effects against C. gloeosporioides on Potato Dextrose Agar (PDA). The mean PIRG (%) of the twelve potential bacterial antagonists were tested using Minitab statistical analysis software which showed that there was a significant difference in mean PIRG (%) with a ratio of 76.81 and an associated p-value of 0.000. Out of the twelve tested bacteria, two isolates, BT12 and BT09 had a significantly higher antagonistic activity against C. gloeosporioides. By using the 16S rRNA technique, isolates BT12 and BT09 were identified as Pseudomonas aeruginosa and Bacillus subtilis while the causal agent of Harumanis mango anthranose was identified as C. gloeosporioides. Both P. aeruginosa and B.subtilis strongly inhibited the fiingal growth by an average of 58.82% and 52.55% and rated at scale 3 using the growth inhibition scale (GIC). Malformation of the fiingal hyphae occurred in the presence of both bacteria which were viewed under light microscopy (LM) and scanning electron microscopy (SEM). Varying degrees of antagonistic effects occurred in the dual culture assay which included the production of antifungal compounds by the antagonist bacteria. The compounds were screened by gas chromatography mass spectrometry (GC-MS). Results indicated that P.aeruginosa and B. subtilis produced antibiotics such as Pyrrolo [1, 2-a] pyrazine-1, 4-dion, hexahydro-, Propanoic acid and Cylohexane, (1, 1-dymethylprophyl) which are responsible for the inhibition of fungal growth. Therefore, in vitro activities of the P.aeruginosa and B. subtilis against C. gloeosporioides of Harumanis mango in thisstudy suggested that the bacteria can be an effective biological control agent.